Developing an Interactive Multimedia Innovation Based on Android Using the Smart Apps Creator 3.0 as Teaching Material for Buffered Solution Course - Rahman, Gusti; Nurfajriani, Nurfajriani; Siti Jahro, Iis (KnE Social Sciences, 2024)
The use of interactive multimedia using Android in chemistry learning materials will make the process of learning more effective, efficient, and interesting. This study focused on developing interactive multimedia using the help of the Smart Apps Creator 3.0 software to improve student learning. This research follows the 4D model development research (Define, Design, Develop, Disseminate). The research sample consisted of 25 students of class XI in a senior high school Grade. The results showed that the interactive multimedia based on Android developed was related to BSNP, with an average acquisition of an eligibility test from a material expert of 3.80 and the average eligibility of a media expert of 3.81 on a scale of 4.00. The learning outcomes of students who were taught using Android-based interactive multimedia were in the high category with an N-Gain value of 0.71, and the learning outcomes obtained by students were higher than the KKM value set at school of 75. These results indicated that this Android-based interactive learning multimedia was appropriate to use as buffered solution material for the high school teaching and learning processes. Keywords: interactive multimedia, android, chemistry, learning materials